Terapia de fotobiomodula????o associada ao exerc??cio f??sico no estresse oxidativo em modelo experimental de artrite reumatoide induzida por col??geno - Santos, Solange Almeida dos (2016)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by chronic and systemic inflammation, which leads to destruction of the cartilage and bone, and affects tissues in multiple joints. Oxidative stress has been implicated in involvement in various disease conditions, such as rheumatoid arthritis (RA). In vivo experimental studies using photobiomodulation therapy (FBM) have shown positive effects in reducing lipid peroxidation and increasing antioxidant activity. The regular practice of physical exercise has also been reported as a beneficial treatment capable of reducing oxidative damage. The aim of this research was to analyze the effect of photobiomodulation therapy at 2 joules and 4 joules doses associated with physical exercise on oxidative stress in an experimental model of rheumatoid arthritis in protein expression: superoxide dismutase (SOD); Glutathione Peroxidase (GPX) and Catalase (CAT) on thiobarbituric acid reactive substances (TBARS). Twenty-four male Wistar rats divided into 4 groups were submitted to an AR model (CIA). First immunization were performed at the base of the tail on the days 0 and 07, and after 28 days the third dose was administered intra-articular in both knees of the animals. After the last induction, FBM therapy was started immediately, transcutaneously at two points: medial and lateral, with a total of 15 applications. Treadmill exercise started the day after the last induction and lasted 5 weeks. As results we obtained the decrease of the lipid peroxidation and the increase of antioxidant activities of SOD, GPX and CAT with physical exercise associated to FBM in doses of 2 joules and 4 joules. Conclusion: Physical exercise associated with FBM therapy decreases lipid peroxidation and increases antioxidant activity.